2015
DOI: 10.4103/0976-3147.153218
|View full text |Cite
|
Sign up to set email alerts
|

Role of bone marrow derived pluripotent stem cells in peripheral nerve repair in adult rats: A morphometric evaluation

Abstract: Objectives:Semi-quantitative and quantitative assessment of the effect of bone marrow-derived mononuclear cells (BM-MNC) on early and late phase of nerve regeneration in rat sciatic nerve model.Materials and Methods:Sciatic nerve transection and repair was performed in 50 inbred female Wistar albino rats divided equally in two groups. In the test group the gap was filled with BM-MNCs obtained from the two male rats and fibrin sealant, while in the control group only fibrin sealant was used. Sciatic nerve was h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…26 Using the same animal model, Kurwale et al applied bone marrow mononuclear cells (BM-MNCs) into the gap between sutured nerve ends and observed significantly higher values for myelin thickness in the treatment group compared with the control (0.41 vs. 0.62 mm). 27 With respect to our control groups, the values of the aforementioned studies corroborate our findings, and thus clearly demon-strate the reproducibility of the animal model as well as validate the utilized methods to quantify nerve regeneration. Interestingly, there was a decrease in axon count from 5 to 9 weeks in both treatment and control groups of our study.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…26 Using the same animal model, Kurwale et al applied bone marrow mononuclear cells (BM-MNCs) into the gap between sutured nerve ends and observed significantly higher values for myelin thickness in the treatment group compared with the control (0.41 vs. 0.62 mm). 27 With respect to our control groups, the values of the aforementioned studies corroborate our findings, and thus clearly demon-strate the reproducibility of the animal model as well as validate the utilized methods to quantify nerve regeneration. Interestingly, there was a decrease in axon count from 5 to 9 weeks in both treatment and control groups of our study.…”
Section: Discussionsupporting
confidence: 85%
“…Frerichs et al applied Clenbuterol to improve regeneration of primary coaptated sciatic nerve injuries in rats and demonstrated an increase in the total nerve diameter from 48 axons per 10,000 µm 2 in the control group to 83 axons per 10,000 µm 2 in the treatment group . Using the same animal model, Kurwale et al applied bone marrow mononuclear cells (BM‐MNCs) into the gap between sutured nerve ends and observed significantly higher values for myelin thickness in the treatment group compared with the control (0.41 vs. 0.62 µm) . With respect to our control groups, the values of the aforementioned studies corroborate our findings, and thus clearly demonstrate the reproducibility of the animal model as well as validate the utilized methods to quantify nerve regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have assessed axon count and myelin thickness to quantify neuronal repair in experimental models . Zor et al demonstrated an increase in axonal and myelinated nerve counts in nerves repaired with hyaluronic acid sheaths and intra muscular vascular endothelial growth factor treatment compared to controls .…”
Section: Discussionmentioning
confidence: 99%
“…BMSCs are skeletal progenitor cells that are easy to obtain, expand in vitro, and transplant in vivo. Previous studies have demonstrated that BMSCs can be differentiated into bone, cartilage, fat and nerve cells, and that BMSCs may be neuroprotective (26)(27)(28). Thus, transplantation of BMSCs into the infarction area and subsequent differentiation into neuronal cells may provide a novel treatment for cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%